Unmasking Evans syndrome: A rare presentation of Schimke immune-osseous dysplasia - Swathi Krishna; Purva Kanvinde; Ritika Khurana; Minnie Bodhanwala; Sangeeta Mudaliar (Elsevier, 2024)
Background: Evans syndrome is an autoimmune condition that manifests as two or more autoimmune cytopenia. We present a case of Evans syndrome diagnosed with an underlying skeletal dysplasia; Schimke immune-osseous dysplasia (SIOD). The condition is characterized by spondyloepiphyseal dysplasia, progressive nephropathy, and T-cell immunodeficiency with cytopenia. Notably, our patient did not exhibit any signs of renal involvement. Case report: A five-and-a-half-year-old female child presented with a short history of bleeding manifestations along with a history of poor weight and height gain. She was subsequently diagnosed with Evans syndrome secondary to an underlying SMARCAL1 mutation, which could be well controlled with oral steroids. Conclusion: SIOD is a rare multisystem disorder affecting the skeletal, renal, immune, and vascular systems. Autoimmune cytopenia was the chief presentation of our patient. Such entities should be suspected in patients with growth failure, bone deformities, and hematological involvement. Early genetic testing will help to reduce disease-related comorbidities and aid in rationalizing treatment strategies.